Breast cancer plus adjuvant chemotherapy- related cognitive impairment: a case study. Issue 3 (4th July 2019) - Fischer, Barbara
ABSTRACT: Breast cancer-related cognitive impairment (CRCI), a frequent concomitant of cancer diagnosis and management, has been difficult to measure objectively. This study longitudinally investigated cognitive function in an individual before and after breast cancer diagnosis and treatment. Comparison of test scores pre- and post- diagnosis/treatment revealed declines in multiple cognitive domains, including Performance IQ, processing speed, immediate auditory and visual memory, and delayed visual memory. Twelve years later, improvements were noted in domains of processing speed, memory and executive functioning. The results highlight the importance of heeding individuals' subjective reports of cognitive decline, and offer hope that such decrements may not be permanent.